A Mixed Method Twitter Methodology and Anonymous Corpus - Tim Ribaric (Journal of Open Humanities Data, 2023)
This dataset represents the first 5 years of posts made by the anonymous twitter bot @lis_grievances combined with a series of custom and pre-established metrics. The bot is a platform for workers in libraries and affiliated fields to make unattributable pronouncements. A simple vetting process ensured no defamatory or explicit posts were made. Anonymity is assured as no evidence of who made the submission is retained, even to the operator of the bot. This dataset represents a collection of thoughts, fears, and cutting remarks made by information workers about their field and the places where they work.